Isorhynchophylline ameliorates stress-induced emotional disorder and cognitive impairment with modulation of NMDA receptors - Wang, Chen; Zhu, Ming-Hao; Sun, Na; Shen, Wei; Jiang, Ning; Zhao, Qin-Shi; Zhang, Yong-Xiang; Huang, Yan; Zhou, Wen-Xia (Frontiers in Neuroscience, 2022)
Isorhynchophylline is one of the main active ingredients from Uncaria rhynchophylla, the effects and mechanisms of isorhynchophylline on stress-induced emotional disorder and cognitive impairment remains unclear. In this study, we found that isorhynchophylline could improve corticosterone-induced in vivo long-term potentiation (LTP) impairment significantly, indicating positive effects on stress. Therefore, 28-days chronic unpredictable mild stress (CUMS) model was adopted to evaluate the anti-stress effects of isorhynchophylline. The results showed that isorhynchophylline improved CUMS-induced weight loss, anxiety- and depression-like behavior, and spatial memory impairment. Isorhynchophylline reduced CUMS-induced corticosterone elevation. Meanwhile, glutamate and the expression of N-methyl-D-aspartic acid (NMDA) receptor (GluN2A and GluN2B), which play an important role in the process of emotion and memory, were increased in the CUMS mice, while D-serine and the expression of serine racemase (SR) decreased significantly, and isorhynchophylline could restore these changes to normal level. These results indicated that isorhynchophylline could ameliorate stress-induced emotional disorder and cognitive impairment, modulating NMDA receptors might be one of the underlying mechanisms.